(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Female circumcision is considered one of the oldest false beliefs and the most penetrating the fabric of customs and traditions. This study dealt with the definition of female circumcision, its types and risks, and the position of the heavenly religions and the Egyptian positive law on it. We concluded that although the recent legislative amendments in Egyptian law related to the criminalization of female circumcision, which attempted to avoid most of the legal loopholes that the ancient texts suffered from. We believe that they will not bear the desired results unless they are integrated with governmental and non-governmental efforts to raise awareness of the dangers of the phenomenon female mutilation. Female circumcision finds its justification in common beliefs, which are deeply rooted beliefs that laws will not be enough to change, unless they are integrated with an educational and awareness program.